Предмет: Алгебра,
автор: Rinka120
4(х-4)(х+8)=(3х+2)(х-5)+(х-1)(х+1)
Ответы
Автор ответа:
0
4(х-4)(х+8)=(3х+2)(х-5)+(х-1)(х+1)
4(x²+8x-4x-32)=3x²-15x+2x-10+x²+x-x-1
4x²+32x-16x-128=4x²-13x-11
4x²+16x-4x²+13x=128-11
29x=117
x=117/29
x=4 1/29
4(x²+8x-4x-32)=3x²-15x+2x-10+x²+x-x-1
4x²+32x-16x-128=4x²-13x-11
4x²+16x-4x²+13x=128-11
29x=117
x=117/29
x=4 1/29
Похожие вопросы
Предмет: История,
автор: mmekv675
Предмет: Английский язык,
автор: asminasaitova12
Предмет: Химия,
автор: Аноним
Предмет: География,
автор: Ликон4ик